1993
DOI: 10.1099/0022-1317-74-12-2737
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in zucchini yellow mosaic virus helper component protein associated with loss of aphid transmissibility

Abstract: Zucchini yellow mosaic virus (ZYMV) is a potyvirustransmitted by aphids in a non-persistent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…The presence of a lysine at position 50, a residue shown to be important in HC-Pro-mediated aphid transmission of potyviruses (Atreya et al, 1992;Atreya & Pirone, 1993), is in agreement with the aphidtransmissible phenotype of this virus (K. Grbrr-S~lassi~, personal communication). No amino acid alterations were observed in regions known to be highly conserved between potyviruses (Granier et al, 1993), except the central CCC box described by Cronin et al (1995) which was CSC in PVY LYE84.…”
Section: Cdna Sequencementioning
confidence: 93%
See 1 more Smart Citation
“…The presence of a lysine at position 50, a residue shown to be important in HC-Pro-mediated aphid transmission of potyviruses (Atreya et al, 1992;Atreya & Pirone, 1993), is in agreement with the aphidtransmissible phenotype of this virus (K. Grbrr-S~lassi~, personal communication). No amino acid alterations were observed in regions known to be highly conserved between potyviruses (Granier et al, 1993), except the central CCC box described by Cronin et al (1995) which was CSC in PVY LYE84.…”
Section: Cdna Sequencementioning
confidence: 93%
“…The N-terminal portion of HC-Pro is required for aphidmediated plant-to-plant transmission (Atreya et al, 1992;Atreya & Pirone, 1993). However, in a recent report a point mutation within the conserved C-terminal proline-threonine-lysine (PTK) box of HC-Pro was shown to be associated with loss of aphid transmissibility of zucchini yellow mosaic potyvirus (Granier et al, 1993;Huet et al, 1994), suggesting that more than one site in HC-Pro could be involved in aphid transmission activity.…”
Section: Introductionmentioning
confidence: 99%
“…The same mutation was also found in a helper-deficient strain of ZYMV from Connecticut (Grumet et al, 1992). For another ZYMV isolate, two mutations were found between the HAT and PAT strains, one of them occurring in a conserved cluster of amino-acids Pro-Thr-Lys (PTK) (Granier et al, 1993). Huet et al (1994) modified the PTK of ZYMV to PAK in an infectious cDNA clone and observed a total loss of HC activity in aphid transmission.…”
Section: Aphid Transmissionmentioning
confidence: 99%
“…Loss of aphid transmissibility can result from a deficiency of the CP (Antignus et al, 1989;Lee et al, 1993) or from the lack of biologically active HC (Lecoq et al, 1991a;Granier et al, 1993).…”
Section: Aphid Transmissionmentioning
confidence: 99%
See 1 more Smart Citation